Risk factors of temporomandibular disorders: literature review : Faktor-faktor risiko gangguan temporomandibular: tinjauan literatur - David Fatola; Syukri Adiputra; Ricca Chairunnisa (Makassar Dental Journal, 2021)
Over recent years temporomandibular disorders (TMD) have been reported to increase in numbers. The TMD is a condition that causes the temporomandibular joint and or chewing muscles not to function normally and is often observed in combinations; covers a large area and has major symptoms like pain, followed by limitations in the mandibular movement, and other clinical problems. If the disorder is not treated immediately, it will cause pathological changes and create more complex conditions. Al-though the risk factors of the TMD are still debated, they nonetheless have been found to be in the development of the disorders. In short, identifying, understanding, and controlling the risk factors may help to prevent the TMD, and more benefits lead to a successful treatment.